Effect of overspeed harness supported treadmill training on running economy and performance - Macaulay, M. R.; Keener, J. R.; Rothenberger, R. (Medicine & Science in Sports & Exercise, 1995)
Ten trained male runners preparing for competition in 21 or 42 km road races used either an overspeed training harness (body weight reduced by 25%) or normal procedures for peaking two days per week. Training intensity was matched using Borg's Rating of Perceived Exertion (RPE). OST training was all at speeds faster than normal. Benefits normally ascribed to overspeed training were not evident in this study. Failure of weight supported OST to produce significant changes may have been due to the use of RPE to set training loads. RPE may not be sensitive to physiological stress during weight supported activities. Implication: Overspeed training showed no benefit for performance improvement over normal running. This is one of the first analyses of this form of training and more research is needed. If one believes in the Principle of Specificity as a true phenomenon, the results of this study are likely to be upheld.